IMPLEMENTASI PERATURAN PENGOPERASIAN PESAWAT TANPA AWAK DENGAN APLIKASI BERBASIS MOBILE PHONE - M HUSNI SYAHBANI (Jurusan Informatika Universitas Jenderal Achmad Yani, 2020)
The increasing use of drones around the world presents a new problem for the aviation world. That makes aviation authority (aviation authority) in several countries issue rules that regulate and control the use of drones. If it is not regulated, the use of drones that are not controlled will increase the risk of endangering flights, especially civil aviation. Safety and security regulations for drone operations in Indonesia are regulated in CASR 107. With the development of current information technology, the implementation of these regulations can be packaged into one mobile application. In this paper, we discuss the concept of mobile application software that can be used to implement these rules. The basic concept of the proposed software was adopted from the B4UFLY software concept developed by the American FAA aviation agency.